Nanoscience and nanoengineering : advances and applications - Kelkar, A. (Ajit), editor; Herr, Daniel J.C., editor; Ryan, James G., editor (Boca Raton : CRC Press, Taylor & Francis Group, 2014)
Includes bibliographical references and index